Cytotoxicity of Printed Aligners: A Systematic Review - Mauro Lorusso; Fariba Esperouz; Gabriele Di Carlo; Michele Tepedino; Rosa Esposito; Giovanni Pappalettera; Caterina Casavola; Lucio Lo Russo; Domenico Ciavarella (Dentistry Journal, 2025)
Background/Objectives: The capability of printing aligners directly, eliminating the need for a dental model or thermoforming, represents a significant advancement in aligner therapy. This review aimed to assess the cytotoxicity of 3D-printed aligners to clarify their safety profile, given their growing clinical use. Methods: An electronic literature search was independently conducted by two reviewers up to February 2025 across PubMed, Scopus, and Web of Science. After a thorough selection process, five in vitro studies were included. The quality and risk of bias were evaluated using the QUIN tool. Results: Five studies were included in the systematic review, four of which used TC-85 resin and one TA-28. Two reported no cytotoxic effects. Mild cytotoxicity was observed in one study using UV and heat post-curing, while another reported increased cytotoxicity with extended UV/nitrogen curing. However, notable heterogeneity was present among the studies in terms of the experimental protocols, the cell lines used, and the outcome measures. Conclusions: The cytotoxicity of printed aligners appears to be influenced by post-curing duration and system type, highlighting the importance of strict adherence to manufacturers’ protocols. Nevertheless, due to the limited number of studies and methodological variability, definitive conclusions cannot yet be drawn. Further clinical and standardised in vitro studies are needed to better assess the biocompatibility of 3D-printed aligners.